Natural Disasters are Punishment: Viewed from the Ecotheology of Islamic Religious Education and Science in the Lubuk Napal Community - Pramadi Pramadi; Z. Zarkasih; Rian Vebrianto (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Phenomena in society show that natural disasters are often understood as a form of punishment from God due to human behavior that damages the environment and violates moral values. This view causes a difference in understanding between religious perspectives and scientific explanations about the causes of natural disasters. The purpose of this study is to analyze the community's view of natural disasters as punishment from the perspective of ecotheology in Islamic Religious Education (PAI) and science. The methodology in this study uses a mix method approach with a case study design. This study involved several respondents from people with different age and occupation backgrounds. The research instrument consisted of a questionnaire consisting of (1) Perception of natural disasters whether punishment, (2) Science perspective on disasters, (3) Perspective on PAI ecotheology, (4) Integration of Religion and Science, (5) Environmental awareness and interview sheets. The data was obtained by distributing the questionnaire through a focus group discussion (FGD). The data obtained was analyzed by trigulation of data to produce comprehensive findings. The results of the study show that some people still view natural disasters as punishment, while the perspectives of ecology and science explain that disasters are also the result of environmental damage and human activities. The implications of this study show the importance of integrating religious and scientific understanding to increase people's ecological awareness in protecting the environment.